Improving Port Performance and Modeling Its Impact Using BPM and BPMN Simulation: A Case Study of Batu Ampar Port - Olifia, Jessica (Pusat P2M Politeknik Negeri Batam, 2024)
This research discusses the cargo terminal at Batu Ampar Batam port. The root cause of the low performance is that the flow of data and information, both internal and external, has not been well systemed. This research helps improve the cargo terminal business processes, especially those related to its dwelling time performance. Business process improvement is carried out by combining BPM methods in the form of streamlining and benchmarking processes and referring to regulations related to the implementation of Inaportnet at ports. In addition, the results of the improvement were also tested for their impact with the simulation method using the BPMN simulation tool, Visual Paradigm. The results of this study indicate that improving business processes with streamlining and benchmarking methods that refer to the application of Inaportnet, can reduce the dwelling time performance of the Batu Ampar Batam port cargo terminal.